2004
DOI: 10.1111/j.1365-2567.2004.01931.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune regulatory effect of pHSP65 DNA therapy in pulmonary tuberculosis: activation of CD8+ cells, interferon‐γ recovery and reduction of lung injury

Abstract: SUMMARYA DNA vaccine based on the heat-shock protein 65 Mycobacterium leprae gene (pHSP65) presented a prophylactic and therapeutic effect in an experimental model of tuberculosis. In this paper, we addressed the question of which protective mechanisms are activated in Mycobacterium tuberculosis-infected mice after immune therapy with pHSP65. We evaluated activation of the cellular immune response in the lungs of infected mice 30 days after infection (initiation of immune therapy) and in those of uninfected mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
1
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 33 publications
6
80
1
6
Order By: Relevance
“…24,25 This vaccine also induced upregulation of MHC class I and class II molecules on macrophages. 26,27 Moreover, different groups have found that mycobacterial hsp65 gene transfer can elicit a profound antitumoral effect. 28,29 The transfection of J774 histiocytic sarcoma cells with the hsp65 gene resulted in reduced tumor development, and immunization with hsp65-transfected sarcoma cells in mice was protective against challenge with unmodified parental tumor cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 This vaccine also induced upregulation of MHC class I and class II molecules on macrophages. 26,27 Moreover, different groups have found that mycobacterial hsp65 gene transfer can elicit a profound antitumoral effect. 28,29 The transfection of J774 histiocytic sarcoma cells with the hsp65 gene resulted in reduced tumor development, and immunization with hsp65-transfected sarcoma cells in mice was protective against challenge with unmodified parental tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, preclinical data from our group and others using different animal models show no evidence of autoimmune disease when DNA-hsp65 was used for immunization. [24][25][26]30 It is relevant to point that the immunogenicity of tumor-derived HSP-peptide complexes has been shown to be individually tumor specific and not tumor-type specific. This suggests that the relevant immunoprotective peptides are most likely derived from individual tumorspecific antigens rather than from shared tumor antigens.…”
Section: Introductionmentioning
confidence: 99%
“…This seems to indicate that host conditions are of particular importance with respect to the effects of mycobacterial Hsp65 on the immune response. In support of this notion are the observations in mice that vaccination with the same DNA-hsp65 construct can induce both strong Th1 immune responses, 5,6,26,27 and regulatory responses marked by production of IL-10, 28,29 depending on the experimental model employed. Once again, the intratumoral route of immunization used in this study may have contributed toward this effect.…”
Section: Discussionmentioning
confidence: 89%
“…The pVAX1hsp65 construction 22 and pVAX1 vector were prepared using the Endo-Free Plasmid Giga kit (Qiagen, Hildenberg, Germany). The endo-free condition of plasmids was determined by the Limulus Amebocyte Lysate test as recommended by European and US Pharmacopoeias, 23 using the QCL 1000 Limulus Amebocyte Lysate test kit (Cambrex, Walkersville, MD).…”
Section: Plasmid Derivationmentioning
confidence: 99%